W perspektywie poznania i projekcji. O polskim przekładzie zbioru esejów Draga Jančara Terra incognita - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2011)
In the Perspective of Cognition and Projection. About a Polish Translation of the Collection of Essays Terra incognita by Drago Jančar In the translation of the essays of Drago Jančar entitled Terra incognita, an intercultural dialogue has been undertaken on the level of lexis within the scope of proper names, making a reader search for the denotements in other regions of Europe. It is not a translation that would speak Slovene in Polish, as Paul Ricoeur accurately defined a translation that would be perfect in shape and more in function. It means that we do not commune with the Slovene culture and with its mentality through the structure and the expression of the Polish language. Despite the undoubted translational intuition of the translator, her language, logical competences and, to a large extent, pragmatically-logical competences, a mental dialogue did not take place between the cultures. Moreover, the translator has used the original title of the book, presenting some other contents of that book. Such abuse of the author’s and receiver’s confidence that is put in a translator changes the view of the rendered text that does not resemble the original. The talent of the author, the effort of the translator and the optimal time of appearing of the translation of the essays caused that the contemporary Slovene essay writing reminds a Polish reader of Jančar, although sometimes of Adam Michnik in a perspective that would make him too alike, of Dubravka Ugešić or of Ivan Čolović.